Evaluating quality of patient-reported outcome measures in patients with hypospadias. Issue 1 (February 2021) - Bhatia, V.P.; Hilliard, M.E.; Austin, P.F.; Mittal, A.G.
Summary: Introduction: There is growing recognition of the importance of patient-reported outcomes (PROs) in pediatric hypospadias. We have previously presented a conceptual framework for Hypospadias-Specific Health-Related Quality of Life (HRQoL), which posited 5 domains of HRQoL in this population. The framework components (domains) included penile appearance, voiding function, social function, psychological/behavioral function, and pubertal/sexual health. In this work, we investigated the established validity and relevance of PROs within each of these domains for patients with hypospadias. Materials and methods: We evaluated existing measures with published psychometric data, including validation data, in the hypospadias population. We also assessed the available data on each measure according to the guidelines of the Scientific Advisory Committee of the Medical Outcomes Trust (Table) in order to establish measure quality. We also examined the power of existing validation studies according to suggested guidelines for psychometric validation and factor analysis. Discussion: Available validated measures in the hypospadias population have focused primarily on penile appearance and to a lesser degree on pubertal development/sexual health. There were no validated disease-specific measures with dedicated evaluations of other key HRQoL domains including voiding-related sequelae, social function, or psychological function. In addition, no single measure addressed all of the quality guidelines posed by the Scientific Advisory Committee. Conclusions: Current generalized measures for PROs lack relevance to the experience of hypospadias patients, and disease-specific assessments are often focused on penile appearance. Improving measure quality is necessary to optimize the value of our assessments and better help our patients with hypospadias. Summary Table SAC Criteria for Measures with Available Psychometric Data in Hypospadias Patients. Summary Table Domain Instrument Reliability Validity Interpretability Responsiveness Respondent Burden Penile Appearance GPS (child/Adult) Yes Yes Adequate Adequate 9 items (Child) GPS (adult) Yes Yes Adequate Adequate 20 items PPPS Yes Yes Unknown Adequate 4 items PPS Yes No Adequate Adequate 4 items HOSE Yes No Decreased Unknown 5 items Social Function (None) a N/A N/A N/A N/A N/A Voiding Function Mini-IPSS No b No Unknown Unknown 21 items Psychological Function PGWBI Yes No Decreased Unknown 22 items Pubertal/Sexual Health BPS (Child) Yes No Unknown Adequate 10 items BPS (Adult) Yes No Adequate Adequate 11 items BESAA Yes Yes Unknown Unknown 30 items SIGHT Yes Yes c Decreased Unknown 11 items a No psychometric data available in the hypospadias population. b See text. The mini-IPSS demonstrated face validity but was not evaluated for construct or content validity. c See text. The SIGHT questionnaire did not demonstrate convergent validity with the Strengths and Difficulties questionnaire.